Elevated plasma levels of vascular permeability factors in C1 inhibitor‐deficient hereditary angioedema. Issue 7 (17th March 2016) - Loffredo, S.; Bova, M.; Suffritti, C.; Borriello, F.; Zanichelli, A.; Petraroli, A.; Varricchi, G.; Triggiani, M.; Cicardi, M.; Marone, G.
Abstract: Background: Hereditary angioedema with C1 inhibitor deficiency (C1‐INH‐HAE) is a rare inherited genetic disease characterized by recurrent swelling episodes of the skin, gastrointestinal tract, and upper airways. Angioedema attacks result from increased vascular permeability due to the release of bradykinin from high molecular weight kininogen. Currently, there are no biomarkers predicting the frequency of angioedema attacks. Vascular permeability is modulated by several factors, including vascular endothelial growth factors (VEGFs) and angiopoietins (Angs). As increased circulating levels of VEGFs and Angs have been observed in diseases associated with higher vascular permeability (e.g., systemic capillary leak syndrome and sepsis), we sought to analyze plasma concentrations of VEGFs and Angs in patients with C1‐INH‐HAE. Methods: Sixty‐eight healthy controls and 128 patients with C1‐INH‐HAE were studied. Concentrations of angiogenic (VEGF‐A, Ang1, Ang2), anti‐angiogenic (VEGF‐A165b ) and lymphangiogenic (VEGF‐C) factors were evaluated by ELISA. C1‐INH functional activity was assessed by EIA. Results: Plasma concentrations of VEGF‐A, VEGF‐C, Ang1, and Ang2 were higher in patients with C1‐INH‐HAE in remission than in healthy controls. Concentration of VEGF‐A was further increased in patients with lower C1‐INH functional activity. Patients with C1‐INH‐HAE experiencing more than 12 angioedema attacks per year were characterized by higher plasma levels of VEGF‐A, VEGF‐C, and Ang2 compared with the other patients. Conclusions: We hypothesize that VEGFs and Angs induce a state of 'vascular preconditioning' that may predispose to angioedema attacks. In addition, the identification of increased plasma levels of VEGFs and Angs in patients with C1‐INH‐HAE may prompt the investigation of VEGFs and Angs as biomarkers of C1‐INH‐HAE severity.